1991
DOI: 10.1007/bf00017914
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mitochondrial DNA instability in Brassica campestris cultured cells

Abstract: We previously showed that the mitochondrial DNA (mtDNA) of a Brassica campestris callus culture had undergone extensive rearrangements (i.e. large inversions and a duplication) relative to DNA of the control plant [54]. In this study we observed that after continued growth, the mtDNA of this culture continues to change, with rearranged forms amplifying and diminishing to varying proportions. Strikingly similar changes were detected in the mtDNA profiles of a variety of other long- and short-term callus and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Because tissue culture has been reported in several instances to induce mitochondrial genome rearrangements (Shirzadegan et al, 1991), we verified that the rearrangements observed in the N and WA-CMS mitochondrial genomes were not caused by the cell cultures used in this study. A similar PCR approach was followed as above, but with DNA templates being total DNA extracted from rice leaves (Supplemental Fig.…”
Section: Validation Of the Rearrangements By Pcrsupporting
confidence: 67%
“…Because tissue culture has been reported in several instances to induce mitochondrial genome rearrangements (Shirzadegan et al, 1991), we verified that the rearrangements observed in the N and WA-CMS mitochondrial genomes were not caused by the cell cultures used in this study. A similar PCR approach was followed as above, but with DNA templates being total DNA extracted from rice leaves (Supplemental Fig.…”
Section: Validation Of the Rearrangements By Pcrsupporting
confidence: 67%
“…Similarly, 133 amplification products generated by 12 arbitrary 10-base primers and six oligonucleotide sequences failed to detect polymorphism among micropropagated plants. Mitochondrial, nuclear rDNA, oligonucleotide DNA probes/primers, RAPD fingerprinting, and nuclear genome size estimation singly or in combination have been effectively used in many studies to detect tissue-culture-induced variation (Breiman et al 1987;Brettel et al 1986;Brown et al 1993;Cecchini et al 1992;Deumling and Clermont 1989;Hartman et al 1989;Isabel et al 1993;Poulsen et al 1993;Rani et al 1995;Rode et al 1987;Shimron-Abarbanell and Breiman 1991;Shirzadegan et al 1991).…”
Section: Pcr-based Oligonucleotide Fingerprintingmentioning
confidence: 99%
“…Moreover, these approaches could not assess the change(s), if any, at the DNA sequence level. During the last few years, molecular markers such as RFLPs (Breiman et al 1987;Chowdhury et al 1994, Shimron-Abarbanell andBreiman 1991;Shirzadegan et al 1991), RAPDs (Bohanec et al 1995;Brown et al 1993;Isabel et al 1993;Rani et al 1995) and oligonucleotide fingerprinting (Poulsen et al 1993;Schmidt et al 1993;Vosman et al 1992) have been found to be of tremendous utility in addressing fundamental and practical questions of plant tissue culture. In the study presented here, we have screened enhancedaxillary-branching-derived Eucalyptus tereticornis and E. camaldulensis plants by RFLP, RAPD, and oligonucleotide fingerprinting markers to assess their genetic fidelity, and to enquire into the applicability of the marker(s) for rapid appraisal of tissue-culture-derived eucalypt plants.…”
Section: Introductionmentioning
confidence: 98%
“…Probing of DNA samples of the five ramets and the mother ortet of each of the three analysed tea clones with DraI, BamHI and EcoRI in combination with probes cob, nad3 and rrn26 gave identical profiles, indicating that the observed variation in the micropropagated plants of C. sinensis clone U26 was not due to any residual heterozygosity in the explant source but was induced by the cultural conditions. Both differences (Shimron-Abarbanell and Brieman 1991; Shirzadegan et al 1991;Hartmann et al 1992;De Verno et al 1994; as well as complete uniformity (Shenoy and Vasil 1992;Rani and Raina 1998b) in mt DNA RFLPs between the mother and meristem-culture derived micropropagated plants have been observed in various plant taxa.…”
Section: Mitochondrial Genomementioning
confidence: 95%
“…Similar observations have been reported in somatic embryo-derived plants of Coffea arabica, wherein the level of somaclonal variation in the mt genome (41%) was much higher than in the nuclear genome (4.38%) . Modifications in the mt genome during in vitro culture might arise through rearrangements, homologous recombination and selective amplification, all of which take place mostly at non-coding hyper-variable regions (Shirzadegan et al 1991). Of the two PCR-based assays used to screen the nuclear genome, ISSR markers, as in Coffea arabica , were more effective in detecting polymorphism among the micropropagated plants of the U26 clone.…”
Section: Issr Fingerprintingmentioning
confidence: 99%